KUALITAS MIKROBIOLOGI JAJANAN ES DI SEKITAR SEKOLAH DASAR (SD) DI WILAYAH PUSAT KOTA, TENGAH KOTA, DAN PINGGIRAN KOTA MALANG - Tamalene, M. Nasir (Green Earth, 2012)
Packed ice snacks are often sold in Elementary School environment at city center area, central city, and suburbs area of Malang. The packed ice snacks were made traditionally by the people using water and the water wells. Schools used as a place to sell by the sidewalk vendors, the school also provided the best-selling to selling ice because the elementary school children with their high activity may cause them thirst, and it will allow them to buy packed ice snacks sold in around the school. Generally, the elementary school students do not know the types of snacks consumed, they just know that by drinking ice can relieve their thirst, other than that they didnât think about the dangers posed by drinking unhygienic ice. By drinking unhygienic ice will cause sickness on students that can affect their learning activities in school. One of types of beverages sold in elementary school is packed ice. Packed ice is likely to be contaminated by pathogenic bacteria which enabling certain standards to ensure the cleanliness. Water and food contaminated by pathogenic bacteria digestive tract is very dangerous to drink, particularly the water that comes from the well which it less qualified microbiology quality.Â Keywords: quality, microbiology, snack ice pack, MPN value, Coliform bacteria, Coliform fecal bacteria, E. coli bacteria.